2020
DOI: 10.1371/journal.pone.0241115
|View full text |Cite
|
Sign up to set email alerts
|

First description and comparison of the morphological and ultramicro characteristics of the antennal sensilla of two fir longhorn beetles

Abstract: Allotraeus asiaticus Schwarzer and Callidiellum villosulum Fairmaire are repeatedly intercepted in wood and wood products all over the world. As two common stem borers of Cunninghamia lanceolata (Lambert) Hooker, to further understanding of the differences in their living habits, behaviors and the mechanism of insect-host chemical communication, we observed the external morphology, number and distribution of antennal sensilla of A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…The beetle being a non-feeding adult, it is apparent that the bacterial units in the electron micrograph constitute autochthonous microbiota, confirming our hypothesis [36]. In other studies, the autochthonous microbiota of the coleopteran gut was found to assist in the production of various hormones such as semiochemicals [37] and sex pheromone in Dendroctonus terebrans hindgut [38]. The number, distribution, and position of antennal sensilla are very crucial for semiochemicals and chemo-receptions in longhorn beetles.…”
Section: Scanning Electron Microscopic (Sem) Study Of P Bigibbosum Gutsupporting
confidence: 81%
“…The beetle being a non-feeding adult, it is apparent that the bacterial units in the electron micrograph constitute autochthonous microbiota, confirming our hypothesis [36]. In other studies, the autochthonous microbiota of the coleopteran gut was found to assist in the production of various hormones such as semiochemicals [37] and sex pheromone in Dendroctonus terebrans hindgut [38]. The number, distribution, and position of antennal sensilla are very crucial for semiochemicals and chemo-receptions in longhorn beetles.…”
Section: Scanning Electron Microscopic (Sem) Study Of P Bigibbosum Gutsupporting
confidence: 81%
“…We expect that chemical communication is rather more complex than it would become apparent from the simple examination of sensilla morphology. Sensilla trichodea prevail also in all hyperdiverse phytophagous beetle lineages of Phytophaga with no increased antennal surface (e.g., Ritcey and McIver 1990;Ranger et al 2017;Vera and Bergmann 2018;Di Palma et al 2019;Dong et al 2020), thus high performance in chemical sensing is not necessarily linked with complicated or highly modified sensilla structure (e.g., Symonds et al 2011). For instance, Rutelinae and Melolonthinae, although having in many lineages quite similar placoid sensilla, differ completely in their pheromone compounds (Melolonthinae: amino acid derivatives and terpenoids; Rutelinae: fatty acid derivatives; Leal 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that the density of sensors is closely related to sensing function (Dong, Dou, et al, 2020; Hu et al, 2020). The Sh II was present at a greater density on the last segment of the labial palps in of females than that of males because female adults need frequent vibrations to acquire feedback from bark when they lay eggs, which was similar to their description on the antennae (Dong, Dou, et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Larval emergence peaks from late March to early April (Nakamura & Kojima, 1981), and adults usually appear from March to May (Cocquempot & Mifsud, 2013). The morphological characteristics of adult C. villosulum have been described in detail (Dong et al, 2020). Callidiellum villosulum beetles are approximately 7–11 mm in length (Cocquempot & Mifsud, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation